Do Social Ties between External Auditors and Audit Committee Members Affect Audit Quality? - He, Xianjie; Pittman, Jeffrey A.; Rui, Oliver M.; Wu, Donghui (The Accounting Review, 2017)
ABSTRACT We examine whether social ties between engagement auditors and audit committee members shape audit outcomes. Although these social ties can facilitate information transfer and help auditors alleviate management pressure to waive correction of detected misstatements, close interpersonal relations can undermine auditors' monitoring of the financial reporting process. We measure social ties by alma mater connections, professor-student bonding, and employment affiliation, and audit quality by the propensity to render modified audit opinions, financial reporting irregularities, and firm valuation. Our evidence implies that social ties between engagement auditors and audit committee members impair audit quality. In additional results consistent with expectations, we generally find that this relation is concentrated where social ties are more salient, or firm governance is relatively poor and agency conflicts are more severe. Implying reciprocity stemming from social networks, we also report some suggestive evidence that audit fees are higher in the presence of social ties between an engagement auditor and the audit committee. Collectively, our analysis lends support to the narrative that the negative implications—namely, worse audit quality and higher audit fees—of these social ties may outweigh the benefits.